The psychological resilience of displaced and non-displaced university students - Sabbar, Aseel Mohammed (Al-Adab Journal, 2015)
The goal of current research to identify significant differences in psychological resilience between university students displaced persons and their peers is displaced , and the research sample of ( 150 ) students(male and female) , researcher prepared the scale, the search results are presence of statistically significant differences in favor of students is displaced